Dark Tetrad and workplace deviance: Investigating the moderating role of organizational justice perceptions - Fernández-del-Río, Elena; Castro, Ángel; Ramos-Villagrasa, Pedro J. (Frontiers in Psychology, 2022)
This study tested the direct effects of Dark Tetrad traits on organizational and interpersonal counterproductive work behaviors (CWBs). We also examined the moderating effects of the three dimensions of organizational justice – distributive justice, procedural justice, and interactional justice – on the Dark Tetrad-CWBs relationships. Based on the data from 613 employees across different occupations, the results revealed that only psychopathy and sadism had significant effects on CWBs targeted at the organization. The results also supported the direct effect of sadism on interpersonal CWBs. The findings confirmed the moderating role of interactional justice but differentially, depending on the dark trait and the target of workplace deviance. Whereas low and medium levels of interactional justice moderated the relationship between Machiavellianism and CWBs directed to the organization, it did not play any role in narcissism, psychopathy, and sadism. Regarding CWBs aimed at other people, interactional justice emerged as a significant moderator in Machiavellianism and sadism. But, whereas sadistic employees performed more harmful behaviors toward other individuals whatever their level of interactional justice, if people high in Machiavellianism (Machs) perceived a high fair interpersonal treatment, they did not show deviant behaviors directed at other employees. The paper concludes with some suggestions and recommendations about the relevance of organizational justice in the influence of dark personality traits on CWBs.